INFLUENCE OF PROFITABILITY AND SOLVENCY ON THE FINANCIAL PERFORMANCE OF TELECOMMUNICATION COMPANIES - Dharma, Ida Bagus Rai Satria; Putri, Aufa Nurristi; Handayani, Wuri; Agusiady, Ricky (Multifinance, 2025)
Purpose This research aims to find out, analyze and describe how much Profitability and Solvency have a partial and simultaneous influence on financial performance. The independent variables in this research are Profitability as measured by Net Profit Margin (NPM) and solvency as measured by Debt to Equity Ratio (DER), while the dependent variable used in this research is Financial Performance as measured by Return on Assets (ROA). The population in this study was 19 Telecommunications Sub Sector companies listed on the Indonesia Stock Exchange (BEI) 2019-2022. Methods, this research sample used a purposive sampling method, thereby obtaining 10 Telecommunications Sub-Sector companies that met the criteria. Result, the research results show that partial Profitability has a significant effect on Financial Performance with a significant value of 0.0000 < 0.05 and Solvency has no significant effect on Financial Performance with a significant value of 0.2515 > 0.05. Finding, Simultaneously Profitability, and Solvency have a significant effect on Financial Performance with a significant value of 0.000000 < 0.05.